2022
DOI: 10.3389/fnins.2022.1013691
|View full text |Cite
|
Sign up to set email alerts
|

Neurodynamic correlates for the cross-frequency coupled transcranial alternating current stimulation during working memory performance

Abstract: Transcranial current stimulation is a neuromodulation technique used to modulate brain oscillations and, in turn, to enhance human cognitive function in a non-invasive manner. This study investigated whether cross-frequency coupled transcranial alternating current stimulation (CFC-tACS) improved working memory performance. Participants in both the tACS-treated and sham groups were instructed to perform a modified Sternberg task, where a combination of letters and digits was presented. Theta-phase/high-gamma-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Intuitively, nodal efficiency captures how efficiently information can be transmitted from a given node to the rest of the network through its immediate neighbors. A node with high nodal efficiency can communicate effectively with other nodes in the network, whereas a node with low nodal efficiency may be relatively isolated from the other nodes of the network ( 72 , 73 ).…”
Section: Methodsmentioning
confidence: 99%
“…Intuitively, nodal efficiency captures how efficiently information can be transmitted from a given node to the rest of the network through its immediate neighbors. A node with high nodal efficiency can communicate effectively with other nodes in the network, whereas a node with low nodal efficiency may be relatively isolated from the other nodes of the network ( 72 , 73 ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 81 ] used optogenetic stimulation to restore memory performance and hippocampal θ – γ PAC in a mouse model of AD. Transcranial alternating current stimulation (tACS) has been recently shown to modulate top-down control and functional connectivity ( θ – γ coupling) across the frontal-occipital regions, leading to enhanced performance in working memory tasks [ 82 ]. Of note, stimulations at the θ – γ frequency over the trough have been found to impair cognitive control [ 83 ].…”
Section: Progress Of Electrophysiological Couplings In Physiology And...mentioning
confidence: 99%
“…As WM mechanisms are frequently associated with patterns of neural oscillations (Axmacher et al, 2010 ; Palva et al, 2010 ; Lisman and Jensen, 2013 ; Roux and Uhlhaas, 2014 ; Sauseng et al, 2019 ), the tACS technique has been especially popular in the ongoing attempts to enhance WM. A number of tACS studies (e.g., Hoy et al, 2015 ; Alekseichuk et al, 2016 ; Feurra et al, 2016 ; Santarnecchi et al, 2016 ; Tseng et al, 2016 ; Möller et al, 2017 ; Borghini et al, 2018 ; Pahor and Jaušovec, 2018 ; Misselhorn et al, 2020 ; Thompson et al, 2021 ; Kim et al, 2022 ; Palm et al, 2022 ; Park et al, 2022 ; Zeng et al, 2022 ; Grover et al, 2023 ; Kvašnák et al, 2023 ) targeted the fast rhythms, such as the gamma (>30 Hz) and, more rarely, the beta band (14 Hz−30 Hz), following the fact that coordinated fast oscillations were linked with active maintenance of particular objects in WM (e.g., Lisman and Jensen, 2013 ; Leszczyński et al, 2015 ). Several such studies reported positive effects of stimulation on WM (e.g., Hoy et al, 2015 ; Alekseichuk et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%